What do you do with success? The science of scaling up a health systems strengthening intervention in Ghana - James F. Phillips; John Koku Awoonor-Williams; Ayaga A. Bawah; Belinda Afriyie Nimako; Nicholas S. Kanlisi; Mallory C. Sheff; Patrick O. Asuming; Pearl E. Kyei; Adriana Biney; Elizabeth F. Jackson (BMC, 2018)
Abstract Background The completion of an implementation research project typically signals the end of research. In contrast, the Ghana Health Service has embraced a continuous process of evidence-based programming, wherein each research episode is followed by action and a new program of research that monitors and guides the utilization of lessons learned. This paper reviews the objectives and design of the most recent phase in this process, known as a National Program for Strengthening the Implementation of the Community-based Health Planning and Services (CHPS) Initiative in Ghana (CHPS+). Methods A mixed method evaluation strategy has been launched involving: i) baseline and endline randomized sample surveys with 247 clusters dispersed in 14 districts of the Northern and Volta Regions to assess the difference in difference effect of stepped wedge differential cluster exposure to CHPS+ activities on childhood survival, ii) a monitoring system to assess the association of changes in service system readiness with CHPS+ interventions, and iii) a program of qualitative systems appraisal to gauge stakeholder perceptions of systems problems, reactions to interventions, and perceptions of change. Integrated survey and monitoring data will permit multi-level longitudinal models of impact; longitudinal QSA data will provide data on the implementation process. Discussion A process of exchanges, team interaction, and catalytic financing has accelerated the expansion of community-based primary health care in Ghana's Upper East Region (UER). Using two Northern and two Volta Region districts, the UER systems learning concept will be transferred to counterpart districts where a program of team-based peer training will be instituted. A mixed method research system will be used to assess the impact of this transfer of innovation in collaboration with national and regional program management. This arrangement will generate embedded science that optimizes prospects that results will contribute to national CHPS reform policies and action.